Positron annihilation in silicon crystals with mechanically processed surfaces; Applied Physics A: Materials Science and Processing; Vol. 8, № 3 - Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich (1975, 1975)
The angular correlation curves of the annihilation photons and the probability of three-quantum annihilation in silicon single crystals with mechanically processed surfaces were measured. The narrowing of the angular correlation curves increases and the three-quantum yield decreases with the depth of the surface abrasion. This is tentatively interpreted in terms of formation of positronium states on the surface of the silicon crystals.